The role of the local authority in the implementation and enforcement of environmental legislation - Riekert, Simon Lodewikus (Department of Private Law, 2024)
This dissertation will initially look at the local authority's constitutional relationships with the national and provincial levels of government. It will then investigate in general the role of the local authority (the local level of government) in the implementation and enforcement of legislation affecting the environment. The various definitions of environment will be discussed indicating that this study will not be limited to the environment as defined in section 29 of the constitution1 • On the other hand it will not consider the built or cultural environment, but will confine the discussion to the natural environment 2 as such, although these matters are briefly referred to when dealing with land development. The legislation that will be dealt with concerns (a) resource utilization, (b) pollution control and waste management and (c) land development and environmental considerations. Resource utilization will not be a distinct topic, but will be considered under the Water Act, the Environmental Conservation Act, vehicle access to the coastal zone, pollution control and land development.